Instructional Media: Increasing Students’ Vocabulary Through Word Cards - Khasanah, Arifatul; Said, Mawardin M.; Nirwana, Nirwana; Kamaruddin, Abdul (Universitas PGRI Adi Buana Surabaya, 2025)
This study aimed to investigate the effectiveness of using word cards in increasing the vocabulary of Grade VIII students at SMP Negeri 3 Sausu. A quasi-experimental design was employed, involving two classes: Class VIII A, consisting of 21 students, served as the experimental class, while class VIII B, with 20 students, served as the control class. The experimental class received instruction using word cards as the treatment, whereas the control class was taught using conventional teaching methods. The samples were selected through total sampling. The study was conducted through a series of procedures, including a pre-test, the treatment, and a post-test. Data were collected using tests, and quantitative analysis was performed to compare students’ scores before and after the treatment. The results indicated a significant difference between pre-test and post-test scores. At a significance level of 0.05, the t-count was 6.62, exceeding the t-table value of 1.68, indicating that the research hypothesis was accepted. These findings demonstrate that the use of word cards is an effective strategy for improving the vocabulary of Grade VIII students at SMP Negeri 3 Sausu. Moreover, the results suggest that word cards positively influence students’ vocabulary retention, as they facilitate better memorization and recall of target words during the learning process as instructional media. However, this study was limited by its relatively small sample size and its focus on concrete nouns and descriptive adjectives. Future research is recommended to involve larger and more diverse samples, as well as a broader range of vocabulary categories, in order to obtain a more comprehensive understanding of the effectiveness of word cards in language learning.